2016
DOI: 10.1016/j.na.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stadium-like domains via boundary value problems for the infinity Laplacian

Abstract: We give a complete characterization, as "stadium-like domains", of convex subsets Ω of R n where a solution exists to Serrin-type overdetermined boundary value problems in which the operator is either the infinity Laplacian or its normalized version. In case of the not-normalized operator, our results extend those obtained in a previous work, where the problem was solved under some geometrical restrictions on Ω. In case of the normalized operator, we also show that stadium-like domains are precisely the unique… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In the same way it can be shown that it is a subsolution by considering the eigenfunction in balls of radius R contained in Ω. Let us mention that in [9] stadium like domains are characterized by considering a Serrin-type problem for the homogeneous infinity laplacian.…”
Section: Examplesmentioning
confidence: 92%
“…In the same way it can be shown that it is a subsolution by considering the eigenfunction in balls of radius R contained in Ω. Let us mention that in [9] stadium like domains are characterized by considering a Serrin-type problem for the homogeneous infinity laplacian.…”
Section: Examplesmentioning
confidence: 92%
“…We mention that cut loci also appear in the studies of other partial differential equations, see e.g. [5,6,11].…”
Section: Introductionmentioning
confidence: 98%
“…The case p = ∞ was also studied in great detail in a series of papers by Crasta and Fragalá, who relaxed the C 2 smoothness of the boundary, see e.g. [7].…”
Section: Introductionmentioning
confidence: 99%